The International Society for Complementary Medicine Research (ISCMR): the Way Forward. Issue 1 (2006) - Lewith, George T; Verhoef, Marja J
Abstract : This article describes the birth and development of the International Society for Complementary Medicine Research (ISCMR) from its inception in 2003. The society's main function is to facilitate the development of CAM research internationally and to use its networks, website, newsflashes and newsletters to communicate with its members and bring CAM researchers together from all over the world.